Assessing the Impact of Human Resource Competency and Employee Commitment on Performance at Urban Republic, a Member of the Erajaya Group, Palembang - Sari, Indah Permata; Heriyanto, Heriyanto (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
Companies must innovate and improve employee performance in today’s competitive business climate to maintain their market share. Urban Republic, a company headquartered in Palembang and part of the Erajaya Group, is the subject of this study, which examines the relationship between employee participation and HR competency and performance. Improving employee performance requires HR competency, including technical and non-technical skills, and employee commitment, characterized by loyalty and dedication. For Urban Republic to remain competitive, they must understand how these elements affect performance. This study aimed to assess the impact of employee commitment and HR competency on performance. Three sections of labor area heads, store leaders, and staff were given surveys as part of the quantitative approach. Multiple regression analysis was used to analyze the data, supported by validity, reliability, and classical assumption tests. The results showed that employee dedication showed almost significant significance, indicating a possible influence, while employee competence had a statistically significant impact on employee performance. Dedication and HR competency significantly impact performance when the two work together. This analysis emphasizes the importance of continuous HR development investment and the potential benefits of employee commitment. To reduce the risk of employee turnover, it is recommended that HR training programs be improved, employee recognition programs be strengthened, commitment issues be addressed, and staff well-being be monitored to avoid burnout. It is recommended that more research be conducted to examine the intricacies of employee dedication and how it impacts work outcomes. The study concluded that a balanced focus on HR competency and employee commitment is essential to optimize employee performance at Urban Republic